Politeness Strategies in Konjo Family Discourse: A Sociolinguistic Study - Agus Rahmat; Syarifuddin Dollah (JELITA, 2026)
This study aims to identify the politeness strategies employed in Konjo family discourse and examine how age and social status shape their use in everyday communication. A descriptive qualitative design within a sociolinguistic framework was employed. Data were collected through audio recordings of naturally occurring conversations among eight members of a Konjo family over a two-week observation period. The recorded interactions were transcribed, translated into English, and analysed using Brown and Levinson’s (1987) politeness theory and Braun and Clarke’s (2006) thematic analysis. The findings reveal that all four politeness strategies bald-on-record, positive politeness, negative politeness, and off-record politeness are present in Konjo family interaction. Positive politeness emerged as the dominant strategy, reflecting affection, solidarity, and emotional closeness among family members. Bald-on-record strategies were primarily used by parents and elders when exercising authority, while negative politeness and off-record strategies appeared mainly in interactions involving respect for elders and humorous exchanges. Furthermore, age and social status strongly influenced the choice of politeness strategies, with younger family members generally responding through compliance, indirectness, or respectful silence. The study concludes that although Brown and Levinson’s framework effectively classify politeness strategies, their realization in Konjo family discourse is deeply shaped by local cultural values, including siri' (honour), respect for elders, kinship, and family harmony. These findings contribute to the growing body of sociolinguistic research by demonstrating the importance of integrating universal politeness theory with culturally specific perspectives.